Pregnancy Massage and Deep Breathing Relaxation Reducing Back Pain in Third Trimester Pregnant Women: Pijat Hamil dan Relaksasi Nafas Dalam Menurunkan Nyeri Punggung Ibu Hamil Trimester III - Sarliana, Sarliana; Hadriani, Hadriani; Ismawati, Suci (Napande: Jurnal Bidan, 2022)
Background: Back pain will affect the quality of life of the mother which has an impact on the mother's pregnancy. The results of interviews with 15 third-trimester pregnant women at the Lasoani Public Health Center showed that 13 pregnant women experienced lower back pain. Massage therapy and deep breathing relaxation are two complementary therapeutic options that can be given to mothers in reducing back pain. The purpose of this study was to determine the effect of pregnant massage and deep breathing relaxation on reducing back pain in third-trimester pregnant women at the Lasoani Public Health Center. The method used is a Pre Experiment design with a one-group pretest-posttest design approach. The sampling technique is consecutive sampling with a sample of = 15, Wilcoxon test data analysis. The results Giving pregnant massage and deep breathing relaxation has an effect on reducing back pain for pregnant women in the third trimester at the Lasoani Public Health Center where at Pre-post 10 pregnant women (67.7%) experienced severe pain levels and during Post-test there was a decrease in pain levels to mild, as many as 10 pregnant women (67.7%). Value sig=0.000<0.05 Conclusion: Pregnancy massage and deep breathing relaxation are effective in reducing back pain for pregnant women in the third trimester at the Lasoani Auxiliary Health Center. It is hoped that the class service for pregnant women can always be improved so that pregnant women who experience complaints, especially low back pain, can be resolved.